2011
DOI: 10.1016/j.ijgo.2011.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotype distribution among French women with and without cervical abnormalities

Abstract: The present data indicate a reduced direct impact of HPV vaccination in the study population owing to a low prevalence of HPV-18 and a high prevalence of HPV-53, HPV-31, and HPV-51.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
10
2
1
Order By: Relevance
“…Our present HPV burden in normal population was comparable with various countries in Europe (1.4-9.2%) (Clifford et al, 2006b). However, it was lower than those generally observed in France (20.2%) (Casalegno et al, 2011), USA (27%) (Evans et al, 2006) and worldwide (10.5%) (Clifford, et al, 2006a).…”
Section: Discussioncontrasting
confidence: 66%
“…Our present HPV burden in normal population was comparable with various countries in Europe (1.4-9.2%) (Clifford et al, 2006b). However, it was lower than those generally observed in France (20.2%) (Casalegno et al, 2011), USA (27%) (Evans et al, 2006) and worldwide (10.5%) (Clifford, et al, 2006a).…”
Section: Discussioncontrasting
confidence: 66%
“…Considering women with normal cervical cytology, when we compared the overall HPV prevalence among Tunisian women with that from neighboring Northern African countries, we reported that it was higher than that of Algeria (5.3%) [22], but lower than that of Morocco (34.3%) [30]. Additionally, we found relatively high HPV prevalence compared to Arab-Muslim countries from the Middle-East [3133] but substantially lower than that reported by other studies of the Sub-Saharan countries [34, 35] and Mediterranean Europe [36, 37]. The different origins and characteristics of the studied population (age, lifestyle, and ethnicity) may be the reason of these disparities in HPV prevalence.…”
Section: Discussioncontrasting
confidence: 45%
“…Yuce et al (2012) reported HPV prevalence as 25.7 (Yuce et al, 2012) and Eroglu detected a positive rate of 32.5% in Kayseri (Eroglu et al, 2011). Studies from different countries which have all used PCR based methods report rates as 7.8% in Iran (Khodakarami et al, 2012), 10.3% in India (Sauvaget et al, 2011), 19.4% in Portugal (Pista et al, 2011, 35.9% in Italy (Piana et al, 2011) and 64.1% in France (Casalegno et al, 2011). There is a wide range between HPV prevalence rates.…”
Section: Discussionmentioning
confidence: 99%